Challenges in the Implementation of Curriculum Based on the Indonesian National Qualification Framework - Magdahalena Tjalla; Abdul Haris Sunubi (JELITA, 2024)
This study was intended to find out the challenges faced by lecturers and students in the implementation of the Indonesian National Qualification Framework Curriculum (INQF) in the English Education Department of IAIN Parepare in three aspects: learning plan, learning process standard, and learning evaluation standard. The questionnaire data were analyzed using the Rasch model to know the item difficulty of curriculum implementation indicators. The data were elaborated through interviews, FGD, and documentation. The study showed that in the learning process aspect, lecturers perceived some items of interactive, holistic, and collaborative indicators were difficult to implement. In addition, in the learning plan, they perceived that compiling lesson plan was easy to implement. They also found no difficulties in implementing the learning process standard indicators such as scientific, effective, and student-centered. Likewise, they found no problems in implementing the learning assessment standard, especially in the techniques and procedures of assessment indicators. Students also perceived some indicators item of the learning process standard were difficult to implement such as holistic, collaborative, contextual, and thematic. In addition, they perceive the assessment procedures indicators items of the learning evaluation standard were not implemented by lecturers. These data suggested that lecturers did not implement these indicators items in the classroom. The research also showed the causes of the difficulties of curriculum implementation: student factors, lecturer factors, and institutional factors.